Strigolactones Improve Plant Growth, Photosynthesis, and Alleviate Oxidative Stress under Salinity in Rapeseed (Brassica napus L.) by Regulating Gene Expression - Ma, Ni; Hu, Chao; Wan, Lin; Hu, Qiong; Xiong, Junlan; Zhang, Chunlei (Frontiers in Plant Science, 2017)
Rapeseed (Brassica napus L.) is a very important edible oil crop in the world, and the production is inhibited by abiotic stresses, such as salinity. Plant hormones can alleviate the stress by regulating the physiological processes and gene expression. To study the plant responses to salinity in combination with GR24, a synthesized strigolactone, the oilseed rape variety (Zhongshuang 11, ZS 11) replications were grown in the pots in a controlled growth chamber under three levels of salinity (0, 100, and 200 mM NaCl) and 0.18µM GR24 treatments at the seedling stage for 7d. The results showed that salinity depressed the shoots and roots growth, whereas GR24 improved the growth under salt stress. Leaf chlorophyll contents, gas exchange parameters (Pn, Gs, Ci and Tr) were also reduced significantly with increasing salinity, and these effects could be partially reversed by GR24 application. Additionally, GR24 treatment significantly increased and decreased the PSII quantum yield (Y(II)) and non-photochemical fluorescence quenching (NPQ) respectively under salinity stress conditions. The activities of peroxidase (POD) and superoxide dismutase (SOD) increased, and lipid peroxidation measured by the level of malondialdehyde (MDA) reduced due to GR24 application. The transcriptome analysis of root and shoot was conducted. 342 common differentially expressed genes (DEGs) after GR24 treatment and 166 special DEGs after GR24 treatment under salinity stress were identified in root and shoot. The DEGs in root were significantly more than that in shoot. qPCR validated that the stress alleviation was mainly related to the gene expression of tryptophan metabolism, plant hormone signal transduction and photosynthesis.